THE UTILIZATION OF THE OPTIMAL MARKETING STRATEGY IN INDONESIAN TOURISM INDUSTRY SECTOR - Tomi Agfianto (Media Bina Ilmiah, 2023)
The decision-making ability in determining marketing strategy is an important thing and must be owned by a sales person. Because the determination of strategy in the marketing sector is needed and cannot be abandoned, as well as marketing in the tourism industry. By determining the right marketing strategy, it is expected to increase the number of existing sales productivity. This paper aims to determine the right marketing strategy model to optimize the number of sales in a tourism industry such as hotels, restaurants, travel agents, transportations and also tourism destinations. The study used qualitative descriptive method and was supported by the literary review with understanding concepts based on secondary data such as books, journals, magazines and the internet. The results showed that there were generally four main components in the determination of marketing strategy, which could be applied as an effort to increase the number of sales in the tourism industry. Those components are called TOUR Model, those are (1) Target means the market which we want to get into, should be clear, (2) Objective means the kind of strategy and marketing mix to get our company goal, (3) Understanding is the way how to evaluate and control the target or goal; and the last is (4) Relationship means customer care should be built in order to keep a loyal guest.